2022
DOI: 10.3389/fmicb.2022.872322
|View full text |Cite
|
Sign up to set email alerts
|

A Cecropin-4 Derived Peptide C18 Inhibits Candida albicans by Disturbing Mitochondrial Function

Abstract: Global burden of fungal infections and related health risk has accelerated at an incredible pace, and multidrug resistance emergency aggravates the need for the development of new effective strategies. Candida albicans is clinically the most ubiquitous pathogenic fungus that leads to high incidence and mortality in immunocompromised patients. Antimicrobial peptides (AMPs), in this context, represent promising alternatives having potential to be exploited for improving human health. In our previous studies, a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
2
6
0
Order By: Relevance
“…The untreated cells had a smooth surface and normal shape, whereas treatment with peptides at fungicidal concentration in HEPES/glucose buffer resulted in damage of the cell surface with leakage of intracellular content, marked with arrows on the figures. Similar observations were shown in a recent work, in which C. albicans cells were treated with the cecropin 4-derived peptide C18 (Sun et al, 2022). The cells treated with ΔM4 showed also a rough surface.…”
Section: Synthetic Peptides δM3 and δM4 Possess Fungicidal Activitysupporting
confidence: 90%
See 2 more Smart Citations
“…The untreated cells had a smooth surface and normal shape, whereas treatment with peptides at fungicidal concentration in HEPES/glucose buffer resulted in damage of the cell surface with leakage of intracellular content, marked with arrows on the figures. Similar observations were shown in a recent work, in which C. albicans cells were treated with the cecropin 4-derived peptide C18 (Sun et al, 2022). The cells treated with ΔM4 showed also a rough surface.…”
Section: Synthetic Peptides δM3 and δM4 Possess Fungicidal Activitysupporting
confidence: 90%
“…A noticeable inhibition of fungal cell filamentation was observed at a concentration of the peptides lower than fungicidal, and it was manifested by the formation of shorter hyphae and decreased expression of genes encoding proteins characteristic for the filamentous form of C. albicans cells (Hwp1, Hyr1, and Als3). A recent study demonstrated a similar effect on C. albicans by the cecropin-derived peptide C18 (Sun et al, 2022). It should be noted that the arresting of fungal cells in the form of blastospores may facilitate their elimination, even at lower peptide concentration.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, antimicrobial peptides (AMPs) have garnered attention for their broad-spectrum antimicrobial activities against bacteria, fungi, and some enveloped viruses [ 9 , 10 , 11 , 12 ], as well as their strong antibiofilm ability [ 13 ]. AMPs are natural, small, and highly conserved effector molecules that play a key role in innate immunity, with the antimicrobial mode of action mainly focused on the integrity of microbial wall cells by pore formation or related activities.…”
Section: Introductionmentioning
confidence: 99%
“…Since the narrow antimicrobial spectrum of Cec4 and its long sequence increased the cost of synthesis, it has been modified to obtain a series of derived peptides with a broader antimicrobial spectrum and smaller molecular weight. Among them, C18 (16 amino acids) has been confirmed to have good antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) and Candida albicans , which also has a certain therapeutic effect against infection in vivo ( 19 , 20 ). Meanwhile, we also found that C9, which has only one amino acid substituted compared with C18, showed good antibacterial activity against S. epidermidis , with an MIC value of 8 μg/mL, which was more than 16 times higher than that of Cec4 (>128 μg/mL).…”
Section: Introductionmentioning
confidence: 99%